The Georgian Population of Occupied Abkhazia and Peace Initiatives - Omar Ardashelia (Соціологічні студії)
Peace initiatives and strategies contribute to the cessation of conflict, the reduction of tension, the establishment of peace, and the initiation of dialogue between opposing parties. These initiatives can take various forms, including: Negotiations and dialogue between the conflicting sides; Mediation, in which a third party (such as an international organization, a foreign country, or a special representative) facilitates communication and agreement between the parties; Reintegration and reconciliation programs, aimed at unifying society after conflict and supporting affected groups through targeted projects; Humanitarian initiatives, including the protection of civilians, the provision of humanitarian aid, and the creation of a stable environment; Educational and cultural programs, which promote a culture of peace, teach tolerance, and help reduce hostility between opposing communities. The objective of this research is to explore the attitudes of the Georgian population living in occupied Abkhazia toward peace initiatives implemented by international organizations, the Georgian government, and third-party states. Naturally, this issue is closely tied to political and socio-economic factors, which are evident both among those displaced from Abkhazia and those still residing under occupation. Gathering the perspectives of the Georgian population living under occupation was challenging but meaningful. Through personal connections and support, we were able to engage with participants. The research focused particularly on which peace initiatives they trust most and which they feel have had a tangible impact on their lives under occupation. Findings indicate that despite various efforts, peacebuilding in the Abkhazian region remains fraught with challenges. Conflict transformation requires more than dialogue and trust-building – it demands socio-economic initiatives that promote equality, security, and sustainable peace for all stakeholders. In this context, peace education and the promotion of a culture of peace are essential, and this process cannot succeed without the active engagement and support of international organizations.